Experimental Evaluation of Avalanche Effect and Hash Consistency in SHA-256, SHA3-256, and BLAKE2b-256 for Smart Grid Data Integrity Verification - Muhammad Ridwan; Rusydi Umar; Muhammad Kunta Biddinika; Puguh Wahyu Prasetyo (Journal of Information System and Informatics, 2026)
Ensuring the integrity of Smart Grid data is essential for preventing unauthorized data modification during transmission and storage. Cryptographic hash functions provide an efficient mechanism for integrity verification; however, their diffusion characteristics and computational performance under identical conditions require further evaluation. This study experimentally compares SHA-256, SHA3-256, and BLAKE2b-256 for Smart Grid data integrity verification using avalanche effect analysis, hash consistency evaluation, and computational performance benchmarking with a standardized 256-bit digest length. The results show that all evaluated algorithms achieved avalanche effect values close to the theoretical 50% criterion (SHA-256: 49.97%, SHA3-256: 49.96%, and BLAKE2b-256: 50.04%) and maintained a 100% hash consistency rate, indicating comparable diffusion capability and deterministic behavior. In terms of computational performance, BLAKE2b-256 achieved the shortest average execution time (11.14 ms), outperforming SHA-256 (13.24 ms) and SHA3-256 (16.87 ms). These findings indicate that all evaluated algorithms are suitable for Smart Grid data integrity verification, while BLAKE2b-256 provides the highest computational efficiency under the experimental conditions. The results are limited to the experimental evaluation of cryptographic hash function behavior and do not represent a comprehensive assessment of Smart Grid cybersecurity.